Number 33 (May 1996) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 1996)
(May 1996) - Geographic Distribution of Eastern and Western Mosquitofishes (Poeciliidae: Gambusia): Delineation of Ranges using Fin Ray Counts. By Robert A. Angus, W. Mike Howell Imperiled Fishes and Aquatic Communities Across The Southern Landscape: Spatiotemporal Data Bases For The 21st Century. By Melvin L. Warren, JP. Regional SFC Reports
Keywords: mosquitofishes; poeciliidae; gambusia